The impact of mobility models on mobile IP multicast research. (9th April 2009) - Xu, Ming-wei; Wu, Qian; Xie, Guo-liang; Zhao, You-jian
The deployment of mobile IP multicast protocols is still rare, research in this area is typically based on simulations. However, many of the previous evaluations were based on a single and simple mobility model; thus, the mobility patterns likely to be exhibited by mobile IP multicast applications are not possible to be obtained. The impacts of different mobility models on the performance of mobile IP multicast protocols are evaluated in the paper. Results show that the protocol performance varies drastically with different mobility models. Two key mobility metrics, number of link changes and multicast agent density, are demonstrated.